STRUCTURAL CHARACTERIZATION AND ATMOSPHERIC ASSESSMENT OF ELEVATOR PITS IN COFFEE DRYING AND PROCESSING SYSTEMS IN THE MUNICIPALITIES OF MUZAMBINHO AND NOVA RESENDE, MINAS GERAIS (REMUNOM, 2026)
In coffee post-harvest facilities and equipment, elevator pits-often located below ground level-may meet or closely approximate the definition of confined spaces, as described in Brazilian Regulatory Standards NR-33 and NR-31. This study aimed to structurally characterize elevator pits used in coffee drying and processing systems and to assess oxygen levels and the presence of atmospheric contaminants. The research was conducted between October 2024 and November 2025 in 12 coffee farms located in the municipalities of Muzambinho and Nova Resende, in southern Minas Gerais, Brazil, totaling 26 evaluated elevator pits. Physical dimensions were measured to estimate internal volume, and atmospheric assessments were performed using a portable multigas detector, without worker entry, employing a sampling pump and hose, with measurements taken at the pit opening and bottom. The analyzed parameters included oxygen (O₂), carbon monoxide (CO), hydrogen sulfide (H₂S), and the lower explosive limit (LEL). The results indicated high structural variability, with an average depth of 2.75 m and a mean volume of 8.96 m³. Oxygen concentrations remained at 20.9% at all evaluated points, with no evidence of oxygen deficiency. Carbon monoxide was detected sporadically in one pit, at concentrations below occupational exposure limits. However, these findings should not be interpreted as a guarantee of safety in all elevator pits within coffee post-harvest facilities, as the observed stability reflects site-specific conditions and does not exclude the possibility of atmospheric changes under particular circumstances. This reinforces the need for prior atmospheric monitoring and preventive risk management in accordance with the guidelines of Brazilian Regulatory Standards NR-33 and NR-31.